Comparing the new concept of impairment in personality functioning with borderline personality disorder: differential psychosocial and psychopathological correlates in a clinical adolescent sample - Wyssen, Andrea; Lerch, Stefan; Reichl, Corinna; Mürner-Lavanchy, Ines M.; Sigrist, Christine; Schär, Selina; Cavelti, Marialuisa; Koenig, Julian; Kaess, Michael (European child & adolescent psychiatry, 2025)
Borderline personality disorder (BPD) is an established diagnosis in adolescence with high comorbidity and psychosocial impairment. With the introduction of the alternative model for personality disorders in DSM-5 (AMPD), personality functioning is operationalized using the Level of Personality Functioning Scale (LPFS), which has been shown to be associated with severity of personality pathology. The present study aimed at examining differential psychopathological and psychosocial correlates of LPFS and BPD. A total of 526 adolescent in- and outpatients were interviewed with the STiP-5.1 (LPFS) and the SCID-II. Mixed linear regression was used to investigate the associations between the two interviews with measures of psychopathology and psychosocial impairment. 11.4% met the diagnostic threshold of both interviews, 16.1% only of the LPFS, and 64.1% were below the diagnostic threshold in both interviews (no PD). The BPD only group was larger than expected—8.4% of patients who met criteria for BPD did not fulfill criteria for significant impairment in the LPFS. The highest burden was found in individuals concurrently showing significant impairment in LPFS and fulfilling BPD diagnosis (LPFS + BPD). Differences between the LPFS only group and the BPD only group were found in risk behavior and traumatic experiences, with higher prevalence in the BPD group. Findings confirm the high psychopathological burden and psychosocial impairment associated with both BPD and LPFS. Those exceeding the diagnostic threshold of LPFS in combination with a BPD diagnosis are characterized by greatest disability. Not all adolescents fulfilling formal BPD diagnosis showed a clinically significant impairment in LPFS, which may refer to a distinct diagnostic group.